Measuring Perceived Research Competence of Junior Researchers - Marrs, Sarah A.; Quesada-Pallarès, Carla; Nicolai, Korinthia D.; Severson-Irby, Elizabeth A.; Martínez-Fernández, J. Reinaldo (Frontiers in Psychology, 2022)
Graduates of doctoral (Ph.D.) programs are expected to be competent at designing and conducting research independently. Given the level of research competence needed to successfully conduct research, it is important that assessors of doctoral programs (e.g., faculty and staff) have a reliable and validated tool for measuring and tracking perceived research competence among their students and graduates. A high level of research competence is expected for all Ph.D. graduates worldwide, in addition to in all disciplines/fields. Moreover, graduates of Ph.D. programs may complete their studies in one country but then obtain a research position in another country, emphasizing the need to ensure that all doctoral programs are fostering similar levels of research competence. Thus, the purpose of this study was to gather additional evidence for validity and reliability of the Research Competence (R-Comp) scale (Böttcher & Thiel, 2018). Specifically, we sought to extend the findings of Böttcher and Thiel (2018) by adapting the scale, translating it to other languages, and applying the tool with a sample of early stage researchers. Our findings provide initial evidence that the adapted PR-Comp is appropriate for use in three languages and across a variety of disciplines/programs of study.